La cuestión de la moralidad del ius gentium en Francisco Suárez - Poncela González, Ángel (Cauriensia, 2023)
The article proposes a rereading of the doctrine of the law of nations according -ius gentium- to the interpretation made by Suárez in the second book of De Legibus. The proximity of the law of nations with natural law led Western jurists and theologians of various eras to consider the law of nations as a special section within natural law and even an order indistinguishable from the natural one. Recognizing, the "eximius doctor", the difficulty of determining the foundation and the object of the law of nations due to its border character, in his legal treatise he will face the task of distinguishing and defining it. For this task he thoroughly reviewed the legal and theological sources commonly used by the scholastic tradition detecting in the intellectualist orientation printed by Thomas Aquinas, a challenge to be overcome. The analysis about the moral character that the precepts of the law of nations may or may not present, offered an opportunity to reach a clear and precise definition of the law itself.